DESIGN AND UPHEAVAL BUCKLING ANALYSIS OF SUBSEA PIPELINE IN BALIKPAPAN BAY USING THE FINITE ELEMENT METHOD - Nur Alifa, Luthfia
Subsea pipelines as an effective means of transportation for the distribution of oil and natural gas need to be designed to meet feasibility standards so that they can operate safely and have a low risk of failure. One of the failures of subsea pipelines is caused by upheaval buckling which occurs due to high temperatures and high pressure acting on the pipe during operating conditions. The occurrence of upheaval buckling is triggered by indentations that form in the pipe when it is laid on the uneven seabed. Large stresses and displacements due to upheaval buckling can cause pipeline failure. In this study, upheaval buckling analysis was conducted using the finite element method with ABAQUS software to determine the influence of the significant difference in seabed elevation and temperature acting on the pipe on the pipeline's stress and displacement. In addition, a subsea pipe wall thickness design was carried out based on the DNV-ST-F101, API RP 1111, ASME B31.8, CSA Z662, and EN 14161 standards. The subsea pipe wall thickness that met the criteria was 12.7 mm. The design of the concrete coating thickness is also carried out based on the DNV-RP-F109 standard. The thickness of the concrete coating that meets the stability criteria is 55 mm with a trenching depth of 15 mm. Based on the results of upheaval buckling modeling analysis, it is observed that at a temperature of 25?, on an even seabed and with a 0.1 m elevation difference, there is von-Mises stress and minimal vertical displacement. However, at an elevation difference of 5.4 m, significant von-Mises stress and vertical displacement occur, reaching 400 MPa and 1.19 m. At a temperature of 150?, substantial von-Mises stress is uniformly distributed along the pipe for both 0.1 m and 5.4 m elevation differences, reaching 470 MPa. Even on an even seabed, it reaches 490 MPa. Vertical displacement is negligible on an even seabed but reaches 5 m when there is an elevation difference. This indicates that at low temperatures, the magnitude of von-Mises stress and vertical displacement are influenced by the seabed elevation difference. On the other hand, at high temperatures, whether at an even seabed or with elevation differences, both von-Mises stress and vertical displacement are significant, unaffected by the seabed elevation difference.